Acupuncture in Australia - O'Sullivan, J; Del Mar, C; Barnes, A; Marron, LJ (Wiley, 2016)
Acupuncture is one of the most commonly accepted forms of alternative therapy in Australia. We have hypothesised that a 2002 World Health Organization (WHO) report on acupuncture, which listed over 90 diseases for which acupuncture may be indicated, but was subsequently withdrawn in 2014, could be contributing to the rise in the popularity of acupuncture. We have determined the prevalence of Australian acupuncturists' websites citing the withdrawn WHO acupuncture report.